Diiodine–Triethylsilane System: Formation of N-Alkylsulfonamides from Aldehydes or Ketones and Sulfonamides - Jiang, Jin; Feng, Siyan; Chang, Jinming (Synlett, 2023)
Reductive amination has not been commonly used in the preparation of N-alkylsulfonamides because of the low nucleophilicity of sulfonamides. In this work, a protocol for the synthesis of N-alkylsulfonamides from aldehydes or ketones and sulfonamides was developed. Molecular iodine, triethylsilane, and ethyl acetate were used as the initiator, reductant, and solvent, respectively. The key role of triethyl(iodo)silane in the reaction was confirmed through control experiments.
Keywords: sulfonamides; reductive amination; iodine; triethylsilane; green solvent